Study of multi-stage multi-effect regenerator for liquid desiccant air-conditioning system - Datta, Nirmalya (2017)
With increasing importance placed on energy efficiency and indoor-air-quality, the advanced energy efficient liquid desiccant assisted air-conditioning (LDAC) systems have attracted attention in the recent years. The thesis aims to develop a vacuum graded LDAC system with multi-stage-effect dehumidification and regeneration systems employing membrane technology namely VMEMD for improving the efficiency of the conventional LDAC system. The proposed multi-effect regeneration test-bed maximizes not only the heat transfer between the heating fluids and salt solution but also mass transfer of water vapour across the hydrophobic membrane. Subsequent findings are obtained through the experimental investigations of multi-effect membrane based LDAC system employing various control parameters of the test facility. We found that the conventional VMEMD is not suitable for the regeneration of LiCl solution for dehumidification purposes. Therefore, the VMEMD system has been modified with one steam three solution (1S-3L) passes system through modelling and simulation. Finally, an experimental investigation is conducted to prove the test-of-concept. The use of 1S-3L is the main findings of this work. The thermal efficiency of the proposed 1S-3L VMEMD system is calculated in terms of performance ratio (PR) and change in feed concentration between the inlet and outlet of the regenerator for various solution flow rates and regeneration temperatures. The proposed system is driven at the lowest temperature of 55°C. The PR value is found ~2 for VMEMD system, which can be considered a new finding.